Investigating the Asymmetric Bimanual Coordination Differences in Male and Female Athletes in Ball and Non-ball Sports - Yaser Khanjari; Elahe Arabameri (Islamic Azad University, Hamedan Branch, 2021)
Objective: Bilateral coordination skills are one of the key factors in performing simple to skillful sports task, so far the differences between ball and non-ball fields have not been determined. Therefore, this study aimed to investigate the differences in asymmetric bilateral coordination between male and female athletes in ballplayers and non-ballplayers. Methods: The samples of this study were randomly selected from the young girls and boys (Mean±SD of age 26.00±4.50) in ball fields (14) and non-ball fields (16) of the Faculty of Physical Education of the University of Tehran. All subjects had complete visual acuity and the consent form of the research. The instrument of Vienna was used to measure peripheral visual. Results: The statistical results of MANOVA test showed that there is significant difference in asymmetrical bilateral coordination between ballplayers and non-ballplayers and girls and boys (P≥0.05). Conclusion: The results of this study showed that asymmetric bilateral coordination performing in ball players had better than non-ball players and girls than boys. According the importance of bimanual coordination skills in the implementation of championship sports, as well as considering gender differences and the positive impact of ball exercises on ball coordination, sports coaches can provide training, especially at a younger age, to facilitate learning of this fundamental skill.